2016
DOI: 10.1016/j.physbeh.2016.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Non-image forming effects of illuminance level: Exploring parallel effects on physiological arousal and task performance

Abstract: This study investigated diurnal non-image forming (NIF) effects of illuminance level on physiological arousal in parallel to NIF effects on vigilance and working memory performance. We employed a counterbalanced within-subjects design in which thirty-nine participants (mean age = 21.2; SD = 2.1; 11 male) completed three 90-minute sessions (165 vs. 600 lux vs. 1700 lux at eye level) either in the morning (N=18) or afternoon (N=21).During each session, participants completed four measurement blocks (incl. one ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
90
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(116 citation statements)
references
References 53 publications
20
90
4
1
Order By: Relevance
“…These measures revealed a clear dissociation between the physiological and cognitive responses to light, as highlighted by neuroimaging studies (Vandewalle et al, 2009) and supported by Huiberts et al (2016). At the physiological level, our temperature analyses showed an effect of lighting.…”
Section: Discussionsupporting
confidence: 72%
“…These measures revealed a clear dissociation between the physiological and cognitive responses to light, as highlighted by neuroimaging studies (Vandewalle et al, 2009) and supported by Huiberts et al (2016). At the physiological level, our temperature analyses showed an effect of lighting.…”
Section: Discussionsupporting
confidence: 72%
“…In line with other studies [4,7,36], the results from the PVT did not corroborate a clear alerting effect of light on behaviour. However, considering this behavioural measure was crucial to our main finding.…”
Section: Discussionsupporting
confidence: 65%
“…Two main findings emerged. First, we dissociated between physiological and behavioural effects of light: blue-enriched light enhanced vigilance as indexed by skin temperature, whereas this physiological effect was not evident at the behavioural level as indexed by the PVT [36]. Second, we found that behavioural effects of light on SART performance were highly variable across individuals, and depended on their prior state of vigilance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the modulatory effects of light on brain network activity in humans are well demonstrated [58], the effects of light on cognitive performance are less clear, with varying results across different behavioural tasks [911,1315,34]. Importantly, the retinal photoreceptors that mediate these responses have remained poorly defined.…”
Section: Discussionmentioning
confidence: 99%